A NEW ERIOPHYID SPECIES (ACARI, ERIOPHYIDAE) FROM A SOLANACEOUS WEED IN A TOBACCO CULTURE IN ARGENTINA - Ballari, Maria Clara; Quinteiros, Sara L. Quintana de; Flechtmann, Carlos Holger Wenzel (REVISTA DE AGRICULTURA, 2014)
A new species of Eriophyidae mite, Tetra gibbosa, is described from all motile stages, from a solanaceous weed, Solanum sisymbrifolium, from a tobacco field in Jujuy, Northern Argentina.